Conquest and revival at Chiantla Viejo: the transition of a highland Maya community to Spanish colonial rule. (October 2022) - Castillo, Victor
Abstract: Abstract : Colonised societies often continue traditional practices in private contexts whilst adopting new forms of ritual in public. Excavations at the Mam centre of Chiantla Viejo in highland Guatemala, however, reveal a more complex picture. Combining archaeological evidence with early colonial documents, the author identifies a revival of Indigenous Maya religion following the Spanish conquest (AD 1525–1550). Despite appearing in colonial records as Christian converts, the Maya directed a sequence of destruction, reconstruction and remodelling of the monumental core of Chiantla Viejo to evoke the landscape of their ancestral settlement of Zaculeu. The results emphasise the importance of public spaces for the persistence of Indigenous religion in early colonial settings.